Decolonizing Knowledge Production and Power Relations in African Studies: Prospects and Challenges (The Strategic Review for Southern Africa, 2023)
Intellectual efforts at removing the vestiges of colonialism in knowledge production and power relations in African studies are not a recent phenomenon. Power relations in this context refer to the binary nature of relations between Africa and the Western world in terms of knowledge production, application and transference. In its chronology, it has been in existence as far as the first decade of independence from European colonialism in the late 1950s.  In spite of the novelty of these cerebral efforts in African studies in the post colonial era, little or no progress has been achieved in its application in our knowledge production processes. Postcolonialism as an intellectual binocular in the social sciences remains an under-explored standpoint even by African researchers in African Universities. Using the theory of Postcolonialism as its framework of analysis with primary and secondary materials, this article examines the prospect of decolonizing the epistemological processes and power relations in African studies. It also examines the factors that are responsible for the slow or no progress that has been achieved in this regard. While the article maintains a positive standpoint about the probability of decolonizing African knowledge and power relations, it concluded that the identified endogenic and exogenic challenges require an adequate attention from all the concerned stakeholders.
Keywords: African Studies; Post-colonialism; International Relations; African Epistemology; Imperialism